Target-shaped combined halo and reversed-halo sign, an atypical chest CT finding in COVID-19 - Shaghaghi, Shiva (Clin Imaging, 2021)
Typical chest CT findings in COVID-19 have been described as bilateral peripheral ground glass opacities, with or without consolidation. Halo sign and reversed halo sign have been reported as atypical imaging findings in this disease. However, to the best of our knowledge, combined presence of these signs has never been reported before. Herein, we present a COVID-19 patient with numerous atypical target-shaped, combined halo and reversed halo pulmonary lesions, in the absence of any other underlying disease.